Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity